The complete mitochondrial genome of Eysarcoris guttigerus (Hemiptera: Pentatomidae) - Chen, Qianquan (Mitochondrial DNA B Resour, 2020)
The mitochondrial genome of Eysarcoris guttigerus has been decoded using Illumina sequencing. The mitogenomic size is 15,368 bp with 42.97% A, 33.90% T, 13.22% C, and 9.90% G. It encoded 13 protein-coding genes, two ribosomal RNA, and 22 transfer RNAs. Phylogenetic tree showed that genus Eysarcoris had a closer relationship with the genus Carbula than the rest of 20 genera.